Comprehensive analysis of two Shank3 and the Cacna1c mouse models of autism spectrum disorder. (5th September 2017) - Kabitzke, P.A.; Brunner, D.; He, D.; Fazio, P.A.; Cox, K.; Sutphen, J.; Thiede, L.; Sabath, E.; Hanania, T.; Alexandrov, V.; Rasmusson, R.; Spooren, W.; et al.
Abstract : To expand, analyze and extend published behavioral phenotypes relevant to autism spectrum disorder (ASD), we present a study of three ASD genetic mouse models: Feng's Shank3 tm2Gfng model, hereafter Shank3/F, Jiang's Shank3 tm1Yhj model, hereafter Shank3/J and the Cacna1c deletion model. The Shank3 models mimick gene mutations associated with Phelan–McDermid Syndrome and the Cacna1c model recapitulates the deletion underlying Timothy syndrome. This study utilizes both standard and novel behavioral tests with the same methodology used in our previously published companion report on the Cntnap2 null and 16p11.2 deletion models. We found that some but not all behaviors replicated published findings and those that did replicate, such as social behavior and overgrooming in Shank3 models, tended to be milder than reported elsewhere. The Shank3/F model, and to a much lesser extent, the Shank3/J and Cacna1c models, showed hypoactivity and a general anxiety‐like behavior triggered by external stimuli which pervaded social interactions. We did not detect deficits in a cognitive procedural learning test nor did we observe perseverative behavior in these models. We did, however, find differences in exploratory patterns of Cacna1c mutant mice suggestive of a behavioral effect in a social setting. In addition, only Shank3/F showed differences in sensory‐gating. Both positive and negative results from this study will be useful in identifying the most robust and replicable behavioral signatures within and across mouse models of autism. Understanding these phenotypes may shed light of which features to study when screening compounds for potential therapeutic interventions. Abstract : SmartCube found different degrees of separation between mutant Shank3/F, Shank3/J mice and Cacna1c mice as compared with their corresponding WT control littermates. As described previously in detail (Brunner et al. 2015), to build a 2D representation of the multidimensional space in which the two groups are best separated, we first find statistically independent combinations of the original features, pick the two new composite features that best discriminate between the two groups, and used them as x‐ and y‐axes (drf 1 and 2; see Appendix Error! Reference source not found.). Each dot represents either a WT (blue) or a mutant (red) mouse. The center, small and large ellipses are the mean, standard error and standard deviation of the composite features for each group. The overlap between the groups is used to calculate the discrimination index, which measures how reliably a classifier can be trained to discriminate between the two groups (the more overlap, the worse the discrimination). (a) The Shank3/F model separates well from the WT group. Note the spread and position variability of the individual mice. (b) The Shank3/J standard deviation ellipse overlaps considerably with the WT control ellipse. (c) The Cacna1c model separates well from the WT group. Note the spread and position variability of the individual mice. n = 13–16 mice per genotype/line.